Answer:15(3x11^+1)
Step-by-step explanation:
Answer:
![h(x)=\dfrac{x}{2}+5](https://tex.z-dn.net/?f=h%28x%29%3D%5Cdfrac%7Bx%7D%7B2%7D%2B5)
Step-by-step explanation:
You are given the function
. To find the inverse function
do such steps:
1. Rewrite the function f(x) as
![y=2x-10](https://tex.z-dn.net/?f=y%3D2x-10)
2. Express x in terms of y:
![y+10=2x\\ \\x=\dfrac{y}{2}+5](https://tex.z-dn.net/?f=y%2B10%3D2x%5C%5C%20%5C%5Cx%3D%5Cdfrac%7By%7D%7B2%7D%2B5)
3. Change x into y and y into x:
![y=\dfrac{x}{2}+5](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7Bx%7D%7B2%7D%2B5)
Now, the inverse function is
![f^{-1}(x)=\dfrac{x}{2}+5](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cdfrac%7Bx%7D%7B2%7D%2B5)
Answer: 5
Step-by-step explanation:
1+1+1+1+1